Grazing management innovation as a strategy to improve animal production and reduce GHG emissions - Marín, Alejandra; Baldissera, Tiago C.; Pinto, Cassiano; Garagorry, Fabio; Zubieta, Angel; Giraldo, Luis Alfonso; Chirinda, Ngonidzashe; Arango, Jacobo; Carvalho, Paulo (2017)
In Colombia, livestock growth appears to be not only inevitable but also desirable for the economy, jobs, and nutrition (FCRN, 2017), grazing systems are now being re-designed to conciliate production with environmental management and improve overall efficiency (Carvalho, 2013). Intensification of cattle production systems is considered as an important strategy for mitigating anthropogenic GHG emissions (Gerber et al. 2013), and improving grazing management is an effective approach for increasing animal productivity while reducing GHG emissions (particularly CH4) per unit of animal product or per unit area. To accomplish these goals, grazing management targets to optimize nutrient consumption per unit of eating time and increase pasture utilization efficiency should be redefined.